Pengaruh Pelatihan Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan Produksi Pada PT. Alasindo Prima di Tangerang - Shinta Audia; Abdul Gani Sidqi; Feriadi Feriadi (Komunitas Dosen Indonesia, 2023)
This study aims to determine the effect of work training and work motivation on employee performance at PT. Alasindo Prima. Job training at PT. Alasindo Prima has a significant influence on employee performance based on employee perceptions as seen from the t test results of tcount 5.079 > ttable 2.000 and sig value (0.00) <0.05. In testing the coefficient of determination Job training has a low influence on employee performance by 55.5% and the remaining 45.5% is influenced by other factors.Work motivation at PT. AlasindoPrima has a significant influence on employee performance as seen from the results of the tcount test, 7.623 > ttable 2.000 and the sig value (0.00) <0.005. In testing the coefficient of determination, work motivation has an influence on employee performance by 70.7% and the remaining 29.3% is influenced by other factors.Training and work motivation at PT. Alasindo Prima has a simultaneous significant effect on employee performance as seen from the results of the F test of Fcount 28.886 > Ftable 2.77 Training and work motivation have an influence on employee performance of 70.9% while the remaining 29.1% is influenced by other factors this is seen in the coefficient of determination test.